A prison mental health network in the RANZCP. (April 2023) - Scott, Russ; Aboud, Andrew; Das, Mrigendra; Nambiar, Narain
Objective: Consider the unique features and challenges of prison psychiatry. Conclusions: A Prison Mental Health Network within the Royal Australian and New Zealand College of Psychiatrists would serve many useful functions including improving the quality of mental health services by promoting high clinical standards and ethical practice by psychiatrists working in prisons.